SRSW Method for Denoising & Super-Resolution of Medical Images - M S, Dalia; Har, Vidya (IJRDO -Journal of Computer Science Engineering, 2015)
High resolution images are needed for many purposes. Medical imaging is one of the importantapplications of high resolution images. Conversion of a low resolution image to a high resolution image isthe main theme. This process is called super-resolution. Non-negative quadratic programming approach isused for getting the non-negative sparse linear representation of the input patch over the low resolutionpatches from the database. The database contains high resolution and low resolution patch pairs. Edges ofthe super-resolved image can be enhanced by using the blind deconvolution technique, there by getting asharp view of the image for treatment and diagnosis